PERSONAL BRANDING OF INSTAGRAM SELEBGRAM @RIANIOND THROUGH SOCIAL MEDIA - Randy Alfredo Samosir Samosir; Leila Mona Ganiem (Universitas Mercu Buana, 2026)
Instagram has become the primary platform for individuals to build their personal brands through visual communication and digital interaction. Through consistent fashion content and a distinctive visual identity, Rian Iond has successfully established himself as a male fashion influencer specializing in the “quiet luxury minimalist” niche. This study aims to analyze how Rian Iond shapes his personal brand on Instagram based on Peter Montoya’s concept of “The Eight Laws of Personal Branding.” The study employs a postpositivist paradigm using a case study method and a qualitative approach. Data were collected through semi-structured interviews, non-participant observation of the Instagram account @rianiond, and digital documentation, and were subsequently validated using source triangulation. The results indicate that Rian Iond’s personal branding is strategically built through a consistent visual identity, with “The Law of Distinctiveness” as the most dominant element. This study concludes that visual differentiation and aesthetic consistency are the primary factors in shaping men’s fashion personal branding on Instagram.